Technological means of ensuring the quality of lubricants - Фукс, И.Г. (Proceedings of National Aviation University, 2009)
In the articles considered basic ways of providing|ADM| of quality of lubricating|lubrication| materials|fabric| are with the purpose of providing|ADM| of the rational use|utillizing|.